In vitro detection of chemical allergens: an optimized assay using mouse bone marrow‐derived dendritic cells. (29th May 2017) - Battais, Fabrice; Huppert, Cécile; Langonné, Isabelle; Muller, Samuel; Sponne, Isabelle
Summary: Background: Identification of the allergenic potency of chemicals is a key step in the safety assessment process. Predictive assays that require no or few animals are needed. Objectives: To develop an alternative in vitro mouse bone marrow‐derived dendritic cell (BMDC) assay to determine the allergenic potential of chemicals. Methods: BMDCs were exposed to well‐known allergens and to non‐allergenic chemicals. Surface marker expression and cytokine release of BMDCs were analysed after treatment. Results: Eleven tested chemicals showed a significant stimulation index (SI) of >1.5 (accuracy, 75%; sensitivity, 69%). The four non‐allergens all showed a SI of <1.5. Eight contact allergens tested showed a significant SI of >1.5 (accuracy, 92%; sensitivity, 89%), whereas only two respiratory allergens showed a significant SI of >1.5 (accuracy, 60%; sensitivity, 33%). Conclusions: The results indicate that the BMDC assay could become a reliable test for assessment of the allergenic potential of chemicals. The next step should include the testing of further chemicals, with the aim of integrating this assay into the toolbox of in vitro methods for the evaluation of the allergenic potential of chemicals.